Thermo‐SPT: A new skin prick test evaluation framework based on low‐cost, portable smartphone thermography - Goktas, Polat; Can Bostan, Ozge; Gulseren, Duygu; Cakmak, Mehmet Erdem; Kaya, Saltuk Bugra; Damadoglu, Ebru; Karakaya, Gul; Kalyoncu, Ali Fuat (Clinical and experimental allergy, 2023)
Background Although the skin prick test (SPT) is a reliable procedure to confirm IgE‐dependent allergic sensitization in patients, the interpretation of the test is still performed manually, resulting in an error‐prone procedure for the diagnosis of allergic diseases. Objective To design and implement an innovative SPT evaluation framework using a low‐cost, portable smartphone thermography, named Thermo‐SPT, to significantly improve the accuracy and reliability of SPT outcomes. Methods Thermographical images were captured every 60 s for a duration of 0 to 15 min using the FLIR One app, and then analysed with the FLIR Tool®. The definition of ‘Skin Sensitization Region’ area was introduced to analyse the time‐lapse thermal changes in skin reactions over several time periods during the SPT. The Allergic Sensitization Index (ASI) and Min–Max Scaler Index (MMS) formulae were also developed to optimize the identification of the peak allergic response time point through the thermal assessment (TA) of allergic rhinitis patients. Results In these experimental trials, a statistically significant increase in temperature was detected from the fifth minute of TA for all tested aeroallergens (all p values <.001). An increase was observed in the number of false‐positive cases, where patients with clinical symptoms not consistent with SPT were evaluated as positive on TA assessment, specifically for patients diagnosed with Phleum pratense and Dermatophagoides pteronyssinus. Our proposed technique, the MMS, has demonstrated improved accuracy in identifying P. pratense and D. pteronyssinus compared with other SPT evaluation metrics, specifically starting from the fifth minute. For patients diagnosed with Cat epithelium, although not statistically significant initially, an increasing trend was determined in the results at the 15 min (ΔT (T15 − T0), p=.07; ASIT15, p<.001). Conclusions This proposed SPT evaluation framework utilizing a low‐cost, smartphone‐based thermographical imaging technique can enhance the interpretability of allergic responses during the SPT, potentially reducing the need for extensive manual interpretation experience as standard SPTs. To improve the accuracy and reliability of skin prick test (SPT) outcomes, an innovative SPT evaluation framework using low‐cost, portable smartphone thermography is presented. The proposed framework has the potential to effectively assess allergen‐induced skin reactions at multiple time points during the SPT, as an alternative to the extensive manual interpretation experience as standard SPTs.